Ambient-temperature properties and mechanistic insights of calcium oxalate-modified low-calcium fly ash geopolymer: Eliminating the need for high-temperature activation - Yue Li; Tianze Song; Hui Lin; Jiale Shen (Case Studies in Construction Materials)
Alkali-activated fly ash geopolymers (FAG) exhibit certain limitations, including prolonged hardening time, as well as slower strength development under ambient temperature conditions. Calcium oxalate can significantly shorten the setting time and effectively balance the compressive strength of fly ash geopolymers at room temperature. Therefore, the properties and reaction mechanism of FAG doped with calcium oxalate at room temperature were studied by measuring setting time, flowability, compressive strength, and using various techniques such as calorimetry, thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and nuclear magnetic resonance (NMR). Results indicated that calcium oxalate effectively improves the hardening properties of FAG. An appropriate amount of calcium oxalate is beneficial for the 28d compressive strength of FAG. Further increasing the content of calcium oxalate reduces the fluidity and compressive strength of FAG. Although the addition of calcium oxalate decreases the reaction rate and cumulative heat release, the addition of calcium oxalate more than 1 % can cause the hydration reaction curve appearing the second accelerated exothermic peak. The improvements of calcium oxalate on the hardening properties of FAG are mainly due to the rapid reactions of the introduced Ca2 + with OH- and the dissolved Si structural units to generate C-S-H gel and Ca(OH)2. An appropriate amount of calcium oxalate can improve the proportion of the Al-rich structural units of Q4(3Al) and Q4(4Al), and increase the mean chain length (MCL) of the formed gel products. However, due to the strong polarization effects Ca2+, further increase the content of calcium oxalate will decrease the fraction of the Al-rich units and the MCL of the formed gel. For this reason, total proportion of the oligomer units increases and the compressive strength decreases.